2016
DOI: 10.1007/s40598-016-0046-6
|View full text |Cite
|
Sign up to set email alerts
|

Open Problems and Conjectures Related to the Theory of Mathematical Quasicrystals

Abstract: Abstractcommon goal of understanding different viewpoints and approaches surrounding the theory of mathematical quasicrystals. The problems below reflect this goal and this diversity and we hope that they will motivate further cross-disciplinary research and lead to new advances in our overall vision of this rapidly developing field.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…In that case, Laczkovich [29,28] (see also [9,37,40]) showed that Theorem 1.2. If n = 2, then X 1 is BD to a lattice if and only if there exist constants c 1 and c 2 such that, for all topological disks U , U 1 − ρ|U | ≤ c 1 + c 2 |∂U |, where |U | is the area of U and |∂U | is the perimeter of U .…”
Section: Introduction and Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In that case, Laczkovich [29,28] (see also [9,37,40]) showed that Theorem 1.2. If n = 2, then X 1 is BD to a lattice if and only if there exist constants c 1 and c 2 such that, for all topological disks U , U 1 − ρ|U | ≤ c 1 + c 2 |∂U |, where |U | is the area of U and |∂U | is the perimeter of U .…”
Section: Introduction and Resultsmentioning
confidence: 99%
“…There has been a burst of activity in recent years studying the bounded displacement (BD) equivalence relation for tilings and Delone sets [16,19,17,18,24,1,39,38]. As we reported in our previous paper [24], there are many relevant papers contributing to the subject that predate the terminology BD such as [7,8,26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These discoveries and production techniques generated an interest in the study of quasiperiodic environments, such that in 2011 the Nobel Prize in Chemistry was given to Schechtman for the discovery of quasicrystals [41]. Such interest continues to grow today, width many open problems from a mathematical point of view [42], and computational challenges, such as the statistical description of the quantum energy levels of a quasicrystal recently addressed with the use of random matrices [43], which also could be related with the length distribution of the free flights in a Lorentz gas [44].…”
Section: Introductionmentioning
confidence: 99%